Anatomical variations in scapes of Eleocharis minima Kunth (Cyperaceae, Poales) - Amphibian and Kranz species - Martins, Shirley; Scatena, Vera Lucia [UNESP] (FapUNIFESP (SciELO), 2015)
In Cyperaceae about 1/3 of the species have Kranz anatomy and some species of Eleocharis can either present Kranz anatomy or not according to the environmental conditions, whether terrestrial (emerged) or aquatic (partly or fully submerged). Eleocharis minima has emerged and submerged scapes in the same individual. To identify the possible differences and their correlation with the environment, the anatomy of these scapes was investigated. The emerged scape is quadrangular e has four vascular bundles, and the submerged is triangular with three bundles. Both scapes (emerged and submerged) show non-Kranz anatomy in the basal region and Kranz anatomy of the eleocharoid type in the median region. In the apical region of submerged scapes occur Kranz anatomy of eleocharoid types, but in this same region of the emerged scape was observed variations in the continuity of the inner bundle sheath and may be interpreted as eleocharoid or chlorocyperoid types. The plasticity of the Kranz anatomy in Eleocharis minima and in other species of the genus is probably related to the amphibious habit. Therefore, the use of characters related to Kranz anatomy in Eleocharis in phylogenetic and evolutionary approaches should be restricted and carefully analyzed in view of its plasticity.
Keywords: Aquatic macrophytes; Eleocharis; Kranz anatomy; Photosynthesis C4; Plasticity